2007
DOI: 10.1167/7.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Holistic crowding: Selective interference between configural representations of faces in crowded scenes

Abstract: It is difficult to recognize an object that falls in the peripheral visual field; it is even more difficult when there are other objects surrounding it. This effect, known as crowding, could be due to interactions between the low-level parts or features of the surrounding objects. Here, we investigated whether crowding can also occur selectively between higher level object representations. Many studies have demonstrated that upright faces, unlike most other objects, are coded holistically. Therefore, in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
174
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(195 citation statements)
references
References 45 publications
15
174
4
2
Order By: Relevance
“…However, we should not preclude the possibility that crowding occurs at multiple levels in the visual system. For example, Louie et al (2007) demonstrated a holistic crowding between high-level face representations, suggesting that face-selective areas (e.g., fusiform face area) might play a role in this kind of crowding (Louie et al, 2007). In the future, it would be important to investigate whether our conclusion can be generalized to other conditions and stimuli.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, we should not preclude the possibility that crowding occurs at multiple levels in the visual system. For example, Louie et al (2007) demonstrated a holistic crowding between high-level face representations, suggesting that face-selective areas (e.g., fusiform face area) might play a role in this kind of crowding (Louie et al, 2007). In the future, it would be important to investigate whether our conclusion can be generalized to other conditions and stimuli.…”
Section: Discussionmentioning
confidence: 84%
“…Fu et al (2010) observed that, when two stimuli were presented in the left and right visual fields, respectively (assuming little interaction between them), the C1 amplitude evoked by the simultaneous presentation of the two stimuli was equal to the sum of the C1 amplitudes evoked by presenting the stimuli separately. Similar to previous neurophysiological (Moran and Desimone, 1985;Miller et al, 1993;Luck et al, 1997) and fMRI studies (Kastner et al, 1998), we defined a suppression index between the target and flankers as (C1 T ϩ C1 F ) Ϫ C1 TϩF for the nearby and far conditions. C1 T and C1 F were the C1 amplitudes evoked by the target (T) and flankers (Near_F or Far_F), respectively.…”
Section: Experiments 1: C1 Suppression and The Target-flanker Distancementioning
confidence: 99%
“…2; all subjects, P Ͻ 0.001). This reduction in discrimination of the target faces with the addition of flankers is due to crowding and has been demonstrated to result from interactions at the level of holistic face information (Farzin et al 2009;Louie et al 2007). Crowding resulted in a drop to chance-level performance in one subject (NS) and slightly above-chance performance in the other three subjects.…”
Section: Resultsmentioning
confidence: 94%
“…1C without flanking faces). Although difficult, observers can still readily recognize faces at this eccentricity (Louie et al 2007;McKone 2004). The faces were presented on a gray background, and each subtended 1.8 ϫ 2.6°of visual angle.…”
Section: Methodsmentioning
confidence: 99%
“…Surrounding a stimulus by similar stimuli (flankers) reduces discriminability of the stimulus, the crowding effect. Adapting to a crowded stimulus does not reduce the adaptation aftereffect for simple features, such as oriented bars at high contrast (He, Cavanagh, & Intriligator, 1996;Rajimehr, Montaser-Kouhsari, & Afraz, 2003 More recent studies suggest, however, that reducing the discriminability of the adapting face by crowding with flanking faces (Louie, Bressler, & Whitney, 2007) reduces the aftereffect for complex stimuli (e.g., faces) at low contrast. Blake et al (2006) resolved this controversy by showing that crowding does not reduce the aftereffect for simple features (e.g., orientation-dependent threshold-elevation aftereffect, TEAE) at high-contrast, but does so for simple features at low contrast, suggesting the existence of response saturation for adapting stimuli at high contrast levels.…”
Section: Introductionmentioning
confidence: 98%